In vitro production of secondary metabolite using Atropa komarovii Bline&Shal (Solanaceae) hairy root culture via Agrobacterium rhizogenes ATCC15834 - Ofelia Banihashemi; Ramazan-Ali Khavari-Nejad; Narguess Yassa; Farzaneh Najafi (Journal of Herbal Drugs, 2017)
Background & Aim:A new sustainable tissue-based system is presented by plant hairy roots, preserving all of the several specialized types of cell with critical roles in allowing bioactive secondary molecules to be synthesized more consistently as usual. The system is also essential for studying the production of alkaloid in culture. Experimental: The Atropa komarovii leaves were wounded and infected with soil gram-negative bacterium Agrobacterium rhizogenes ATCC15834. After three weeks, the transformation roots and control roots without infection, appeared, and for confirming that T-DNA Ri plasmid fragments were transformed and integrated to plant genome, the rolB gene region, was amplified using PCR. HPLC method was then used for assaying how two tropane alkaloids such as atropine (hyosciamine) and scopolamine (hyoscine) were produced in hairy roots,control roots, leaves and roots of plantlet. Results: The data indicated that diagnostic 500bp rol B product amplification was exhibited to be present by all the transformed hairy roots. Scopolamine content in hairy roots was considerably greater than that in control roots but greatest (Hyoscyamine) atropine content was observed in control roots. Analysis of DW, FW and root length showed that fresh and dry root weight increased in hairy roots compared with that in non transformed root. Recommended applications/industries: The present study demonstrated that secondary metabolite production using medicinal plants concerns many researchers worldwide today and hairy root culture is a useful method for producing tropane alkaloids in solanaceae.